THE IMPACT OF INDIVIDUALIZED HOMEOPATHY IN TREATMENT OF PRIMARY DYSMENORRHOEA– A CASE REPORT - DR. SHWETA MOHANBHAI PATEL; DR. RAKESH GOHEL (The Bioscan, 2026)
Primary dysmenorrhea (PD) is a major burden for many women, particularly adolescents, significantly impacting their daily lives and academic performance due to frequent absences caused by menstrual pain. This condition, characterized by painful menstruation, commonly presents as sharp or dull pelvic or lower abdominal discomfort and is often bad enough to force them to miss out on school and work. Primary dysmenorrhea (PD) is menstrual pain in otherwise healthy young women with no underlying physical issues. In contrast, secondary dysmenorrhea is caused by a pelvic disease and sometimes requires surgery. Treating PD often involves the use of homeopathic remedies, which have demonstrated considerable efficacy. This evidence-based case report, following CARE guidelines, suggests the potential of individualized homeopathic medicines as a safe and effective treatment option for primary dysmenorrhea. A recent case study involving a 23-year-old patient demonstrated how effective personalized homeopathic treatment can be. The patient had been experiencing severe cyclic lower abdominal pain during menstruation for the past eight years and was regularly taking painkillers to cope. Homeopathic intervention, initially with Sabina and later with Crocus sativa based on symptom totality and repertorisation, led to a significant reduction in pain and overall improvement. Pain levels were monitored using a visual analogue scale (VAS). Keywords Primary dysmenorrhoea, Individualized treatment, Homoeopathy, Sabina, Crocus sativus.